Pengaruh Motivasi Kerja terhadap Kinerja Karyawan (Study pada PT. Bank BNI Cabang Kota Malang) - Ismunawan Ismunawan; Amin Catur Saputro (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
The purpose of the study was to determine whether or not there is an influence related to work motivation on the performance of employees at PT. Bank BNI Malang City Branch. So in accordance with these objectives, this research includes a type of quantitative research that is causal or causal, and is also included in descriptive research (Explanatory Research). Employee Performance (Study at PT.Bank BNI Malang City Branch)", it can be concluded as follows: Related to work motivation, it is known that the responses of respondents agreed and strongly agreed with the statements that had been submitted on the research questionnaire. So from the results of these studies, it can be concluded that work motivation on employee performance at PT. Bank BNI Malang City Branch is said to be good. This is evident from the work motivation of employees at PT. Bank BNI Malang City Branch has a significant effect on Employee Performance of PT. Bank BNI Malang City Branch. Keywords: Motivation, Job Performance, HRM